Chlamydia pneumoniae immunoglobulin E antibody levels in patients with asthma compared with non-asthma. Issue 2 (February 2020) - Smith-Norowitz, Tamar A.; Loeffler, Jeffrey; Huang, Yvonne; Klein, Elliot; Norowitz, Yitzchok M.; Hammerschlag, Margaret R.; Joks, Rauno; Kohlhoff, Stephan
Abstract: Chlamydia pneumoniae is an obligate intracellular bacterium that causes respiratory infection in adults and children. There is evidence for an association between atypical bacterial pathogens and asthma pathogenesis. We sought to determine whether past C. pneumoniae infection triggers C. pneumoniae - IgE antibodies (Abs) in asthmatics and non-asthmatics, who had detectable IgG titers. C. pneumoniae IgE Abs were quantified using enzyme immunoassay (EIA). C. pneumoniae IgE Ab levels were higher in asthmatics compared with non-asthmatics. There was no correlation found between total serum IgE levels and specific C. pneumoniae IgE Ab levels. C. pneumoniae infection may trigger IgE-specific responses in asthmatics. Abstract : Infectious disease; Biological sciences; Health sciences; Immunology; Asthma; Chlamydia pneumoniae ; Immunoglobulin E.